2023
DOI: 10.2147/pgpm.s376083
|View full text |Cite
|
Sign up to set email alerts
|

Are We Ready for Whole Population Genomic Sequencing of Asymptomatic Newborns?

Abstract: The introduction of genomic sequencing technologies into routine newborn screening programs in some form is not only inevitable but also already occurring in some settings. The question is therefore not “if” but “when and how” genomic newborn screening (GNBS) should be implemented. In April 2022, the Centre for Ethics of Paediatric Genomics held a one-day symposium exploring ethical issues relating to the use of genomic sequencing in a range of clinical settings. This review article synthesises the panel discu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 11 publications
(23 citation statements)
references
References 53 publications
0
14
0
Order By: Relevance
“…However, its costs are low, at less than $5 per infant, including downstream costs [ 26 ]. gNBS is likely to be at least 50 times more expensive [ 5 ]. Despite knowing this, in focus groups, participants demonstrated strong preferences for gNBS to be publicly funded to mitigate potential inequities and to benefit the taxpayer overall by saving healthcare costs in the long term.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…However, its costs are low, at less than $5 per infant, including downstream costs [ 26 ]. gNBS is likely to be at least 50 times more expensive [ 5 ]. Despite knowing this, in focus groups, participants demonstrated strong preferences for gNBS to be publicly funded to mitigate potential inequities and to benefit the taxpayer overall by saving healthcare costs in the long term.…”
Section: Discussionmentioning
confidence: 99%
“…However, some have suggested that the Wilson and Jungner criteria are outdated in the genomics era, as they rely on decisions being made on a condition-by-condition basis [ 4 ]. In reality, the vast number of conditions that could be screened using genomic sequencing makes this case by case model impractical moving forward [ 5 ]. The evolving clinical landscape and growing interest and availability of genomic sequencing technologies has prompted reconsideration of the appropriateness of these criteria in the modern age since these technologies were introduced [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Today, NBS programs around the world are highly successful, operating in many countries at relatively low cost with near-universal uptake [ 5 ]. The level and detail of informed consent required for traditional NBS varies by jurisdiction; in many countries, consent for traditional NBS is implied [ 6 ], yet overall, population trust and uptake remain high [ 7 ].…”
Section: Introductionmentioning
confidence: 99%